Strategic Sectors in the Knowledge Economy and Development in the City of Madrid and its Region - Sánchez-Moral, Simón; Díez-Pisonero, Roberto; Gago-García, Cándida; Arellano-Espinar, Alfonso (Revista de Estudios Andaluces, 2019)
Different international agendas (OECD, Europe 2020) consider the promotion of knowledge based activities and innovation. The objective of this research is to analyze the strategic role of high technology-intensive industries, knowledge-intensive services and the cultural industries in Madrid. The paper begins by reviewing the approaches to strategic sectors in large European capitals. The analysis of firm networks in the region confirms the importance of these sectors in Madrid’s global connections and the articulation of their economic flows, but also the heterogeneous nature of the temporal and spatial trends of employment. Without losing sight of the tendency by large cities to replicate the selection of similar strategic sectors, their role in urban and regional development strategies would have a solid base in the case of Madrid.